Leptin levels in patients with systemic lupus erythematosus inversely correlate with regulatory T cell frequency. (November 2017) - Wang, X; Qiao, Y; Yang, L; Song, S; Han, Y; Tian, Y; Ding, M; Jin, H; Shao, F; Liu, A
Leptin levels are increased in patients with systemic lupus erythematosus (SLE) but little is known on how this correlates with several disease characteristics including the frequency of regulatory T cells (Tregs). Here we compared serum leptin levels with frequency of circulating Tregs in 47 lupus patients vs. 25 healthy matched controls. Correlations with lupus disease activity were also analyzed, as well as Treg proliferation potential. It was found that leptin was remarkably increased in SLE patients as compared to controls, particularly in SLE patients with moderate and severe active SLE, and the increase correlated with disease activity. Importantly, increased leptin in lupus patients inversely correlated with the frequency of Tregs but not in controls, and leptin neutralization resulted in the expansion of Tregs ex vivo. Thus, hyperleptinemia in lupus patients correlates directly with disease activity and inversely with Treg frequency. The finding that leptin inhibition expands Tregs in SLE suggests possible inhibition of this molecule for an enhanced Treg function in the disease.